Dikotomi Pendidikan Agama Islam Dan Pendidikan Umum di Indonesia - Badrut Tamami (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2019)
Dichotomy in education merely aims at creating a system for compartmentalization or restrictions on practitioners in the world of education, differentiating between religious with general education, state-based with private-based schools, centralistic education and independent self-reliance in a policy, as well as in terms of facilities and resources, employment, and human resources. As a form of embodiment in fostering education for moral values and moral character, education on Islamic religion at school is crucial to form good personality of students who have a fundamental principle of carrying out the commands of Islamic law and avoiding being prohibited, and implementing the value of worship in daily activities vertical in nature with the creator and horizontal fellow humans with courtesy and ethics. The method in this paper is the result of a critical analysis of some phenomena in the world of education in Indonesia and took several references, articles, journals by concluding that there is a dichotomy between the majority of Islamic religious education and public education as the majority of people as steak holders. between these differences without them know about such issues. The author formulates with a title: Dichotomy in Islamic and General Education in Indonesia.